Online Shopping and Human Factors - Issa, Tomayess (Springer, 2014)
The purpose of advertising on the Internet is to promote and sell products, services and information around the world. This media is considered a quick access to information and is luring customers away from queues at shopping malls and turning them to the conveniences of the Internet. However, the online market can bring various drawbacks, which make the consumers hesitate about buying products online. This study is restricted to investigating two drawbacks of online shopping: the lack of face-to-face human interaction and lack of physical touch. These factors need to be addressed by online retailer in order to avoid the possible frustration experienced by consumers who are using online media. These problems can be prevented by addressing three factors in the user interface design of a website. Firstly, Human–Computer Interaction (HCI) and usability evaluation need to be considered in user interface design to increase the efficiency of the staff, thereby increasing profits, and to address the issue of safety. Secondly, navigation, interaction and feedback need to be taken into consideration by the website developer as they provide easy access, friendly interface, and human interaction. Thirdly, in order to improve consumer satisfaction, reduce operational costs and increase revenue, several methods and tools can be adopted such as 3DCart, NetSuite, and SensAble Technologies. Results from this study show that when these factors have been taken into consideration, a big difference is made to customer support services as most consumers are motivated and encouraged to revisit the Web business more often. On the other hand, this study points out that more research needs to be done in website design, especially in relation to the end-user who has disabilities.